Drought-tolerant and drought-sensitive genotypes of maize (Zea mays L.) differ in contents of endogenous brassinosteroids and their drought-induced changes - Tůmová, Lenka; Tarkowská, Danuše; Řehořová, Kateřina; Marková, Hana; Kočová, Marie; Rothová, Olga; Čečetka, Petr; Holá, Dana (PloS one, 2018)
The contents of endogenous brassinosteroids (BRs) together with various aspects of plant morphology, water management, photosynthesis and protection against cell damage were assessed in two maize genotypes that differed in their drought sensitivity. The presence of 28-norbrassinolide in rather high quantities (1-2 pg mg-1 fresh mass) in the leaves of monocot plants is reported for the first time. The intraspecific variability in the presence/content of the individual BRs in drought-stressed plants is also described for the first time. The drought-resistant genotype was characterised by a significantly higher content of total endogenous BRs (particularly typhasterol and 28-norbrassinolide) compared with the drought-sensitive genotype. On the other hand, the drought-sensitive genotype showed higher levels of 28-norcastasterone. Both genotypes also differed in the drought-induced reduction/elevation of the levels of 28-norbrassinolide, 28-norcastasterone, 28-homocastasterone and 28-homodolichosterone. The differences observed between both genotypes in the endogenous BR content are probably correlated with their different degrees of drought sensitivity, which was demonstrated at various levels of plant morphology, physiology and biochemistry.
Keywords: Photosynthesis; Brassinosteroids; Plant Growth Regulators; Plant Leaves; Stress, Physiological; Zea mays; fyziologický stres; genotyp; kukuřice setá; období sucha; regulátory růstu rostlin; brassinosteroidy; Droughts; fotosyntéza; Genotype; listy rostlin